Antenatal Screening for Hepatitis B and Antibodies to Toxoplasma gondii and Rubella Virus: Evaluation of Two Commercial Immunoassay Systems - Diepersloot, Robert J. A. (American Society for Microbiology, 2001)
A comparative evaluation of the Abbott AxSYM and DPC Immulite random-access analyzers was performed using 497 prospectively collected serum samples. These samples were sent to the laboratory for routine antenatal screening for hepatitis B surface antigen and immunoglobulin G (IgG) and IgM antibodies to Toxoplasma gondii and rubella virus. The overall agreement between the two assay systems ranged from 97.4 to 100%. After discrepancy analysis, the outcome in terms of sensitivity and specificity varied from 98.2 to 100% for all but one of the assays tested. The AxSYM rubella virus IgG assay tended to report protective or indeterminate antibody levels in 1% of the samples. This shortcoming might be overcome by raising the cutoff of the microparticle enzyme immunoassay system.